A Qualitative Comparison of Cross-Border QRIS and Global Card Networks - Adita, Dharma; Widiyanto, Ariq; Megawati, Liya (STMIK Indonesia Banda Aceh, 2026)
This study examines the strategic role of Cross-Border Quick Response Code Indonesian Standard (QRIS) as a transformative alternative to conventional international payment systems, specifically comparing its operational efficiency and cost structure against Visa and Mastercard networks. Employing a descriptive qualitative method and secondary data synthesis from 2020–2025, the study explores linkages between Indonesia, Malaysia, and Singapore within ASEAN’s digital payment ecosystem. Findings demonstrate that Cross-Border QRIS significantly reduces transaction costs through lower Merchant Discount Rates (MDR) and accelerates settlement under the Local Currency Settlement (LCS) framework. Additionally, it contributes to regional “dedollarization” and enhances digital sovereignty by fostering domestic control over payment infrastructure and transaction data. Despite these advantages, card networks remain superior in global coverage and fraud prevention. The research concludes that an optimal payment ecosystem requires a hybrid adoption model combining QRIS efficiency with the international reach of card schemes.